Talent development program in higher education institution: an investigation of students' leadership profile - Aini Nazura Paimin,; Mohamad Khairi Aliashak,; Muhammad Hakim Ahmad,; Mohd Faisal Hushim,; Noreina Kepal,; Riyaz Ahmad Mohamed Ali,; Radin Dewistiawati Radin Mohamed,; Muhammad Hafizul Amin Jimaain, (Penerbit Universiti Kebangsaan Malaysia, 2024)
One of the challenges in ensuring sustainability leadership among students in the context of higher education institutions is through the talent formation strategy at the residential college level. This study was conducted to identify differences in the student leadership profile of residential college students who participated in a talent development program held at a Malaysian university. This survey study involves a total of 183 participants among residential college student leaders to identify the student leaders' leadership profile from the aspects of creativity, communication, collaboration, critical thinking, autonomy, perseverance, and emotional intelligence. The study identified differences in the student leadership profiles before and after implementing the talent development program. The study's findings show that students' creativity, thinking skills, and perseverance were high before and after the program. Communication and collaboration have successfully been improved due to the program, while aspects of autonomy and emotional intelligence remain moderate. It is recommended that universities plan more focused activities in the talent development program and identify better strategies for developing student leadership characteristics, especially in autonomy and emotional intelligence.